2020
DOI: 10.33007/inf.v6i3.2459
|View full text |Cite
|
Sign up to set email alerts
|

Pemberdayagunaan Imbal Hasil Wakaf Uang Melalui Sukuk: Regulasi, Implementasi, Dan Modelnya Untuk Pemberdayagunaan Usaha Mikro, Kecil, Dan Menengah Di Indonesia

Abstract: UMKM memiliki peran strategis dalam pembangunan ekonomi nasional, bahkan dapat bertahan dari krisis yang terjadi pada 1997-1998 di Indonesia. Sayangnya, ketangguhan UMKM ini tidak berarti apa-apa dihadapkan COVID-19. Cash Waqf Linked Sukuk (CWLS) yang merupakan hasil integrasi dari wakaf tunai dengan Suku Negara hadir di tengah ancaman krisis dari COVID-19. Kemanfaatannya dapat dijadikan sebagai sarana pembangunan nasional dan kesejahteraan sosial, termasuk perberdayaan UMKM. Tulisan ini merupakan penelitian p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
5
0
1
Order By: Relevance
“…This diagram summarizes the research approach used in research methodology related to CWLS in the scientific literature. It can be concluded that in the realm of research on CWLS, the dominant prevalence was found in the form of qualitative investigations in the form of literature studies with a percentage of 64.71% Afrianti, 2022;Anindhita et al, 2022;Armen et al, 2022;Cahyono et al, 2022;Hafandi et al, 2021;Indra et al, 2020;Istikomah et al, 2021;Lailatullailia et al, 2021;Maesarach et al, 2022;Mudriqoh, 2023;Mukti et al ., 2022;Nugroho et al, 2022;Puspitasari et al, 2022;Putri et al, 2020;Rahayu et al, 2020;Rahman et al, 2021;Maulina, 2022;Sa'idaturrohman , ;Sasongko et al, 2021;Siswantoro, ;Sulaeman et al, 2022;Tanjung & Agus, 2021 ;Ubaidilaah & Wahyu, 2021;Winarto et al, 2021; ANP (Afifah et al, 2022 ;Rabbani et al;Suratman et al, 2023) (Nurjamil, 2021), content analysis (Wati et al, 2022) and SLR Joseph, 2022).…”
Section: Cluster 4: Cwls Research Methodology (Additional)mentioning
confidence: 99%
“…This diagram summarizes the research approach used in research methodology related to CWLS in the scientific literature. It can be concluded that in the realm of research on CWLS, the dominant prevalence was found in the form of qualitative investigations in the form of literature studies with a percentage of 64.71% Afrianti, 2022;Anindhita et al, 2022;Armen et al, 2022;Cahyono et al, 2022;Hafandi et al, 2021;Indra et al, 2020;Istikomah et al, 2021;Lailatullailia et al, 2021;Maesarach et al, 2022;Mudriqoh, 2023;Mukti et al ., 2022;Nugroho et al, 2022;Puspitasari et al, 2022;Putri et al, 2020;Rahayu et al, 2020;Rahman et al, 2021;Maulina, 2022;Sa'idaturrohman , ;Sasongko et al, 2021;Siswantoro, ;Sulaeman et al, 2022;Tanjung & Agus, 2021 ;Ubaidilaah & Wahyu, 2021;Winarto et al, 2021; ANP (Afifah et al, 2022 ;Rabbani et al;Suratman et al, 2023) (Nurjamil, 2021), content analysis (Wati et al, 2022) and SLR Joseph, 2022).…”
Section: Cluster 4: Cwls Research Methodology (Additional)mentioning
confidence: 99%
“…The leveraging of returns can be realized through models such as in-kind, qard al-hasan, and mudhārabah, all of which have different implications and benefits in supporting Micro, Small, and Medium Enterprises (MSMEs) actors in Indonesia. This shows the flexibility and creativity in utilizing returns to achieve broader goals (Indra & Hakim, 2020). Furthermore, it is important to understand that returns from CWLS management have a much bigger role than just financial returns.…”
Section: • the Third (Blue) Cluster Is Cwls Developmentmentioning
confidence: 99%
“…The development of CWLS has also shown great potential in overcoming several economic and social challenges, especially in dealing with dynamic global situations such as the COVID-19 pandemic (Nur, 2022). Through CWLS, Islamic financial actors can optimize financial resources to support development programs, such as education, health, and community economic empowerment (Indra & Hakim, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The government will issue a special series of State Sukuk "SW" which also has special features, including a three-year tenor, non-tradable, payment of benefits at a discount and a fixed rate of return paid periodically. The government will use the profit of the issuance of the SW series State Sukuk to finance the APBN, including to finance the development of public service projects such as the construction of educational infrastructure and religious services (Indra & Hakim, 2020;Rahayu & Agustianto, 2020;Nezliani, 2021).…”
Section: Introductionmentioning
confidence: 99%